Collective Knowledge and Experience for Resource-Focused Business Continuity Plans Foundation: Survey on How Home-Visit Nursing Operators in Japan Coped with the COVID-19 Pandemic - Kanno, Taro; Umemoto, Mizuki; Ishida, Chie; Iguchi, Aya; Okada, Risa; Kanesaka, Takayuki (Journal of disaster research, 2023)
This paper presents a nationwide survey about how Japanese home-visit nursing stations prepared and coped with the coronavirus disease 2019 COVID-19 pandemic. This study also aimed to provide a practical foundation and guide to develop business continuity plans (BCPs) for home-visit nursing stations and nursing care facilities to cope with pandemics. We applied a resource-focused BCP framework to efficiently collect and summarize knowledge and experiences from many facilities about the responses and countermeasures based on the three fundamental purposes to keep resources: prevent loss, promote increase, and utilize limited resources. We conducted a survey during Japan’s third wave of the COVID-19 pandemic and analyzed the responses using a qualitative and inductive content analysis method. We could develop categories to summarize various responses and countermeasures in a consistent and comprehensive manner. Based on the analysis results, we proposed six fundamental sub-plans to reorganize resource-focused BCP. The categorization and sub-plans are not special or innovative; however, since they focus only on resources and explain what we need to consider in BCPs in terms of action plans for resources, we expect that it is easier for BCP non-experts to understand the concept and utilize it for developing practical responses and countermeasures.